Can definite integral solve the 'aul problem? - Musthofa, Muhammad Wakhid; Malahayati, Malahayati (Universitas Islam Negeri Raden Intan Lampung, 2022)
There is a similarity in concept between 'aul and the definite integral. 'Aul deals with the issue of the quantity of inheritance which must be divided into smaller quantities in order to be handed over to the heirs, while definite integral relates to the problem of calculating the broad of an area by dividing the area into smaller ones, followed by summing up the broad of each area. Achmad Yani used the definite integral to solve the problem of 'aul. But, in our opinion, the concept he used was wrong and there were still some errors in the construction that he described. This article aims to provide some corrections to such errors and provide some notes that as far as our research, the definite integral has not been able to be used in solving the problem of 'aul yet.